Review paperCardiovascular safety of antihistamines - Olasińska-Wiśniewska, Anna; Olasiński, Jerzy; Grajek, Stefan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Histamine is a mediator, which increases the permeability of capillaries during the early phase of allergic reaction, causes smooth muscle contraction of bronchi and stimulates mucous glands in the nasal cavity. Antihistamines are the basis of symptomatic treatment in the majority of allergic diseases, especially allergic rhinitis, allergic conjunctivitis, urticaria and anaphylaxis. The cardiotoxic effects of the two withdrawn drugs, terfenadine and astemizole, were manifested by prolonged QT intervals and triggering torsades de pointes (TdP) caused by blockade of the ‘rapid’ IKr potassium channels. These phenomena, however, are not a class effect. This review deals with a new generation of antihistamine drugs in the context of QT interval prolongation risk.